Perancangan Jaminan Kualitas Kehalalan Produk Makanan Berdasarkan Metode Failure Mode Effect Analysis (FMEA) (Studi Kasus: UMKM Cilok ABC) - Putra, Ronald Ivo Crisnadianta (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2024)
Cilok is a type of traditional snack from West Java made from tapioca flour. Based on observations, the cilok production process includes activities that have the risk of reducing the halal assurance of the product. Therefore, this study aims to identify any reduction in halal assurance using the Failure Mode and Effect Analysis (FMEA) method to ensure halal compliance by business operators. Based on the results of identification by identifying halal assurance by determining the Risk Priority Number (RPN) based on a scale on severity (severity), level of occurrence (occurrence) and level of occurrence (detection), revealed eleven risks of reduced halal assurance. The next step is to propose improvements to implement halal assurance measures, following the given recommendations to maintain the product’s halal status.